Analisis Nilai Tambah Pengolahan Ubi Ungu di PO. Imo Syrup Denpasar - REYDELT SAPLORI JOI TAMSAR; I WAYAN BUDIASA; I GAA LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Analysis of the Value Additional Processing Of Purple Sweet Potato in PO. Imo Syrup Denpasar PO. Imo Syrup Denpasar is the business processing a purple sweet potato into syrup and juice so as to be durable and provide value added of a product. The purpose of this study is to determine the size of value added of purple sweet potato as the raw materials of syrup and juice and to calculate provit level obtained the company. The research analysis used of the value added Hayami and BEP method with cycles once process production. The research results showed that 10 kg purple sweet potato become 18,75 L syrup and value added is Rp 59.660/L syrup, processing 10 kg purple potato became 15L juice and value added Rp 72.500/L juice. Advantages of gained for one of a production peocess is Rp.52.760 /L Syrup and foe juice is Rp 65.600/L. This effort is also supported by the acquiremwnt on syrup worth Rp.10.416.666 or in break event condition can be obtained by selling as much syrup 221,63/L with selling price Rp.6.693/L. At the minimum sale of juice or in breakeven points Rp.1.736.111 or to produce a much 126,08 L with selling price Rp.980,85/L. Financially PO. Imo Syrup Denpasar can be said profitable. The sugestion that can be given to company is do the promotion by social media. so that the people knows about benefit of and an existanceof juice and syrup purple sweet potato.